2014
DOI: 10.1080/10548408.2014.873312
|View full text |Cite
|
Sign up to set email alerts
|

Representations of a Destination City Break. Analysis Based on Free Associations

Abstract: The article demonstrates the interest in using social representations as a tool of analysis in the representation of city breaks for two generational cohorts. The main objective of this study is to identify and to compare social representations of a city break for Generation X and for Baby Boomers. The article is based on a review of the generational segmentation and the social representation literature. The results indicate no difference between both generations for strong and numerous associations but a diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Word association tasks constitute one of the main methods for collecting the content of SRs. It can be supported by a number of studies dealing with various objects of SR whose content has been revealed by verbal associations (for recent works see Dany, Urdapilleta, & Lo Monaco, ; Ernst‐Vintila, Delouvée, & Roland‐Lévy, ; Jung & Pawlowski, , ; Mäkiniemi, Pirttilä‐Backman, & Pieri, ; Lebrun, ; Mouret, Lo Monaco, Urdapilleta, & Parr, ; Piermattéo, Lo Monaco, Moreau, Girandola, & Tavani, ; Pozzi, Fattori, Bocchiaro, & Alfieri, ; Roland‐Lévy, Lemoine, & Jeoffrion, ; Salès‐Wuillemin et al, ; Tavani, Zenasni, & Pereira‐Fradin, ). Two methods are based on this type of task: free associations and hierarchical evocations (see Dany et al, for a recent review).…”
Section: Methods For Studying the Structure And Organization Of Sociamentioning
confidence: 79%
“…Word association tasks constitute one of the main methods for collecting the content of SRs. It can be supported by a number of studies dealing with various objects of SR whose content has been revealed by verbal associations (for recent works see Dany, Urdapilleta, & Lo Monaco, ; Ernst‐Vintila, Delouvée, & Roland‐Lévy, ; Jung & Pawlowski, , ; Mäkiniemi, Pirttilä‐Backman, & Pieri, ; Lebrun, ; Mouret, Lo Monaco, Urdapilleta, & Parr, ; Piermattéo, Lo Monaco, Moreau, Girandola, & Tavani, ; Pozzi, Fattori, Bocchiaro, & Alfieri, ; Roland‐Lévy, Lemoine, & Jeoffrion, ; Salès‐Wuillemin et al, ; Tavani, Zenasni, & Pereira‐Fradin, ). Two methods are based on this type of task: free associations and hierarchical evocations (see Dany et al, for a recent review).…”
Section: Methods For Studying the Structure And Organization Of Sociamentioning
confidence: 79%
“…The amateur athletes were asked by the organizers of the event, a local sports association, to complete an online questionnaire while professional athletes had to complete a printed version. Lévy, 2011;Jung & Pawlowski, 2014, 2015Authors, 2016;Mäkiniemi, Pirttilä-Backman, & Pieri, 2011;Lebrun, 2014;Authors, 2013;Authors, 2014;Pozzi, Fattori, Bocchiaro, & Alfieri, 2014;Roland-Lévy, Lemoine, & Jeoffrion, 2014;Tavani, Zenasni, & Pereira-Fradin, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…An initial study was conducted using the free ranked association method (Lo Monaco et al, 2017). Word association tasks are widely used in the field of SRs (Dany, & Pawlowski, 2014Lo Monaco et al, 2016;Mäkiniemi, Pirttilä-Backman, & Pieri, 2011;Lebrun, 2014;Lo Monaco et al, 2017;Pozzi, Fattori, Bocchiaro, & Alfieri, 2014). The aim of this study was to highlight the various features related to laptops.…”
Section: Study 1: Cue Identificationmentioning
confidence: 99%